Les évangéliques, l’Honorable Compagnie des Indes Orientales et la christianisation du sous-continent indien au tournant du XIXe siècle - Evelyne Hanquart-Turner (Revue Française de Civilisation Britannique)
The Evangelical interest stretching out to the various Societies for Promoting Christianity as well as the House of Commons, the City and the East India Company played a central part in the development of British colonial power. Two major aspects of Evangelical action are analysed here: firstly, the controversy about the Company territories’ accessibility to missionaries and, as a corollary, the behaviour expected from the Company as paramount power towards native religions and their practices, which were sometimes disturbing for the Christian proprietors; secondly, after 1813, the foundation of the first Indian bishopric of the Church of England, with strongly Evangelical bishops, leading to decisive choices in terms of education and public life, but rather inconsequential for the subcontinent’s conversion to Christianity.